Behaviour of self-repaired reinforced concrete beams made using smart materials under static cyclic loads (shear study). (January 2022) - Hassan, Haysam S.; Elkhatib, Ali A.; Ahmed, Mohamed M.; Al-Tamimi, Adil K.
Abstract: The aim of the study is to work on developing a pump automatic system capable of supplying the repair materials into expected cracks in shear or tension zones by internal injection epoxy materials. It functions once it receives the signal from crack sensors to measure (crack width and strains) in order to commence the injection after any sudden impact in the structure occurs. The new strengthening methods were experimentally investigated for simply supported concrete beams with internal injected ducts and /or super elastic Nitinol bars under static load in two cycles (loading – off loading) up to failure with different shear reinforcement ratio. The studied parameters were the type of strengthening technique and shear reinforcement ratios. This is in addition to their effect on the loads, deflections, concrete, steel and Nitinol smart bar strain as well as ductility and stiffness that were also analyzed for all tested beams. Results elucidated that the ultimate load of beams having both internal injected ducts and super elastic Nitinol bars has increased by 12% compared with the reference beams; moreover, the deflection and concrete strain at the ultimate load decreased by 31% and 30% respectively. Furthermore, steel and Nitinol strains had small recovery behavior passed 85% of the ultimate load up to the failure due to the effect of the strain recovery of the smart bars.